The Influence of Values and Attitude toward Healthy Food Selection at Student of Bogor Agricultural University - Syah, Aidha; Yuliati, Lilik Noor (Department of Family and Consumer Sciences, Faculty of Human Ecology, IPB University, 2017)
The food selection is a process that consumers do every day before consuming any food. The food which is selected for consumption will have an effect for our health. This study aimed to analyze the influence of values and attitudes toward healthy food choices. Design research was using cross sectional study with a survey method using a self-report questionnaire and involving 288 students of PPKU IPB selected by cluster random sampling technique. Data were analyzed using SPSS for descriptive, different test of an independent t-test, correlation analysis and multiple regression analysis. The results showed that there are significant differences in values and attitudes between men and women and meanwhile there was no significant difference in the selection of healthy foods between men and women. Values and attitudes of students have a positive relationship to the choice of healthy foods. The results also showed that the attitude had a positive and significant effect on the choice of healthy foods, otherwise values had no significant effect on the choice of healthy foods.